Maternal and Infant Risk Factors on The Incidence of Neonatal Asphyxia in Bali: Case Control Study - Ni Nyoman Ayuk Widiani; Desak Putu Yuli Kurniati; I Gusti Ayu Trisna Windiani (Universitas Udayana, 2016)
Background and purpose: Indonesia Demographic and Health Survey (IDHS) in 2012 showed neonatal mortality rate (AKN) in Indonesia amounted to 19/1000 live births. The causes were respiratory distress or asphyxia (35.9%), premature delivery, low birth weight (32.4%) and sepsis (12%). Neonatal asphyxia in the last 5 years at Sanglah Hospital in Denpasar relatively stagnant namely: 2010 (8.6%), 2011 (9.3%), 2012 (11.6%), 2013 (8.3%), and 2014 (11.3%). This study aims to identify risk factors of mothers and infants to neonatal asphyxia. Methods: The study design was a case control with a sample of 172 infants of 86 cases and 86 controls were selected randomly from the birth register at Sanglah Hospital in 2015 and matched by age of gestation. Cases were neonatal (0-28 days) born with asphyxia, while control were neonatal without asphyxia. Data analysis was performed using univariate, bivariate (chi square test) and multivariate using logistic regression. Results: The study finding showed that significant risk factors which increased the incidence of neonatal asphyxia were nuchal cord with adjusted OR (AOR)=6.55 (95% CI: 2.34 to 18.33); anemia during pregnancy with AOR=6.49 (95% CI: 2.21 to 19.03); prolonged labor with AOR=6.27 (95% CI: 1.37 to 28.70), low birth weight with AOR=3.85 (95% CI: 1.61 to 9.18); maternal age <20 years and >35 years with AOR=3.57 (95% CI: 1.48 to 8.61) and hypertension during pregnancy with AOR=2.40 (95% CI: 1.06 to 5.44). Conclusion: Mathernal and infant factors that increased risk of neonatal asphyxia were nuchal cord, anemia during pregnancy, prolonged labor, low birth weight, maternal age <20 years and >35 years and hypertension during pregnancy.